2021
DOI: 10.1016/j.xkme.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Utilization of Home Dialysis: An Action Agenda From the First International Home Dialysis Roundtable

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…This finding is also consistent with what has been found in previous studies [ 12 , 13 ]. Additionally, these findings have prompted leading global kidney disease organisations to advocate for increased access and uptake of PD to minimise infection rates among dialysis patients, an especially vulnerable group to worse outcomes [ 14 ]. This would also hold true in the event of any pandemic that might hit in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is also consistent with what has been found in previous studies [ 12 , 13 ]. Additionally, these findings have prompted leading global kidney disease organisations to advocate for increased access and uptake of PD to minimise infection rates among dialysis patients, an especially vulnerable group to worse outcomes [ 14 ]. This would also hold true in the event of any pandemic that might hit in the future.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the global trends in PD catheter insertion procedures and the impact of COVID-19, an electronic questionnaire was administered to 82 nephrologists from 17 countries (Appendix B). The target audience of this voluntary survey was clinicians involved in starting patients on home dialysis taken from the mailing lists from the International Home Dialysis Roundtable [ 65 ] (Table 2 ).…”
Section: Practice Before and During Covid-19mentioning
confidence: 99%
“…This underutilization can be explained by inadequate awareness of PD among physicians and patients, a dearth of trained medical personnel, and a lack of advocacy for it as a viable KRT modality [ 5 , 6 ]. Nevertheless, leading global kidney disease organizations have been increasingly advocating for increased access and uptake of PD [ 7 ], especially after the COVID-19 pandemic hit, as many studies have demonstrated lower infection rates among PD patients compared to their HD counterparts [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%